Cardiac and respiratory standstill during sleep. Issue 9 (September 1978) - Shaw, T R; Corrall, R J; Craib, I A
Abstract : An obese man, with an attack of myocardial ischaemia, developed arrhythmias only when he was asleep. Episodes of sinus bradycardia occurred progressing to arterioventricular block and sinus arrest. These changes in the cardiac rhythm coincided with periods of sleep apnoea.